Efecto de la concentración y temperatura de panela y miel de abeja en la osmodeshidratación de nabo (Brassica rapa L.) asistido por ultrasonido - Cerna Alfaro, Eduar Joel (2019)
The objective of this research was to evaluate the effect of the temperature and concentration of honeycomb and panela solutions on the kinetics and diffusion coefficient of mass transfer in turnip osmodehydration (Brassica rapa L.) assisted with ultrasound. For this, a 2k factorial design + 3 central points was established, with the concentration of the osmotic medium (panela and honey) as independent variables between 30 – 60 °Brix and the temperature (30 – 60 °C). The turnip was conditioned in 1.0 cm edge cubes and monitored during the 7-hour osmodehydration process, for which the samples were subjected to ultrasound compared to one without movement. The results indicate that regardless of the type of osmotic agent used, the application of ultrasound considerably improved the loss of water and gain of solids by the turnip, losing up to 54.07 and 48.50% in the solutions of panela and honey, respectively. While there was a maximum solids gain of 16.50 and 20.69% in solutions of panela and honey, respectively. The diffusivity coefficients in the ultrasound treatment (40 kHz) in the panela solutions varied between 3.12 – 3.89 x 10-10 m2/s and between 2.05 – 2.93 x 10-10 m2/s for water and solids respectively, while that in the control treatment (without movement) the diffusivity coefficients varied between 1.41 – 1.84 x10-10 m2/s and between 0.83 – 1.56 x 10-10 m2/s for water and solids respectively. Also, in the osmodehydration of the turnip in honey bee solutions in the ultrasound treatment (40 kHz) the diffusivity coefficients for water and solids varied respectively between 2.84 – 3.58 x 10-10 m2/s and between 2.08 – 3.01 x 10-10 m2/s, although in the treatment without movement (control) it varied between 1.10 – 1.65 x 10-10 m2/s and between 0.98 – 1.62 x 10-10 m2/s for water and solids respectively. The analysis of variance indicated a statistically significant effect (p < 0.05) by the independent variables on the diffusivity coefficient.